Effects of metacognitive listening strategy training on listening comprehension and strategy use of ESL learners - Abdul Malik, Faridah; Sarudin, Isarji; Muhamad, Ainon Jariah; Engku Ibrahim, Engku Haliza (IDOSI Publications, 2013)
This paper reports on a quasi experimental research investigating the effects of metacognitive listening strategy training on ESL learners’ listening comprehension and the metacognitive listening strategy used. The subjects of the study were 54 students enrolled in a 14-week pre-university English programme. During the training, 29 students in the experimental group were provided with a list of metacognitive strategies and their descriptions and were taught how to use them,while 25 students in the control group took the normal listening course as prescribed by the host institution. The findings of the study based on ANCOVAshowed that students who underwent metacognitive listening strategy training performed slightly better than students in the controlgroup. The difference, however, was not statistically significant. Nevertheless, they had widened their strategy repertoire and used these strategies more frequently, reflecting characteristics of good listeners.